2018
DOI: 10.1016/j.vas.2017.12.001
|View full text |Cite|
|
Sign up to set email alerts
|

Serum chemistry and gut morphology of two strains of broiler chickens to varying interval of post hatch feeding

Abstract: This trial was carried out to determine the responses of two broiler strains of chicken to different post-hatch access to feed. 180-day old chicks (Arbor acre and Marshal strains) with initial weight range of 39.36–42.24 g were used for this study. Each strain was divided on weight equalization into three treatment groups consisting of three time-periods with access to feeds (4 h, 24 h, 48 h) post hatch in a 2 × 3 factorial experiment after which they were fed ad-libitum. Thirty (30) bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
1
13
1
1
Order By: Relevance
“…At the starter phase, the values of Serum biochemical indices recorded were within range with those reported by Adeleye et al. (2018) who evaluated the serum chemistry of broiler chickens at varying intervals of post hatch feeding although, uric acid and creatinine values were slightly higher.…”
Section: Discussionsupporting
confidence: 81%
“…At the starter phase, the values of Serum biochemical indices recorded were within range with those reported by Adeleye et al. (2018) who evaluated the serum chemistry of broiler chickens at varying intervals of post hatch feeding although, uric acid and creatinine values were slightly higher.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that higher serum protein and lower globulin values were observed in more efficient (lower FCR) birds due to superior utilization of nutritional protein ( Adeleye et al., 2018 ). These results agreed with the present study where lower FCR and greater BW of Ross male broilers was associated with lower GLOB values, when compared to Cobb broilers; and greater TP values when compared to female broilers.…”
Section: Resultsmentioning
confidence: 99%
“…(2005) using hematological profiling. While other studies have focused on hematological and biochemical reference ranges only with regard to a specific time, strain, region, or sex ( Adeleye et al., 2018 ; Al-Nedawi, 2018 ; Nanbol et al., 2016 ), others have studied the effects of various treatments on hematology including feeding allopurinol to reduce uric acid levels ( Klandorf et al., 2001 ) or the effect of heat stress on similar blood biomarkers ( Wang et al., 2018 ). Regardless of the objective, these hematological profiling experiments have occurred with increasing frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric results of the duodenum, jejunum, and ileum in broilers on day 42 of the experiment revealed that DDP treatment enhances the health of the digestive tract by altering the villus height and crypt depth. Absorption of nutrients is promoted by longer villi and shallower crypts with greater surface area, which activates maturation of the intestinal cells and digestive enzyme activity (35,36). The crypt is the production site where divisions of stem cells occur to allow villus renewal.…”
Section: Discussionmentioning
confidence: 99%